Treatment Adherence and Its Associated Factors among Cancer Patients Receiving Chemotherapy at a Tertiary Cancer Center in Chitwan, Nepal - Panthee, Sabita; B.K , Prativa; Upadhyay , Hari Prasad (Journal of College of Medical Sciences-Nepal, 2026)
Background Cancer is a major public health problem and leading cause of morbidity/mortality worldwide. Chemotherapy is one of the main treatment modalities for cancer management. The objective of study was to find out the treatment adherence and associated factors among cancer patients receiving chemotherapy. Methods A cross-sectional study was carried out to assess treatment adherence and associated factors among cancer patients receiving chemotherapy. In this study 100 cancer patients were included. Non probability purposive sampling was used to select the sample and data was collected by structured interview schedule and analyzed by using SPSS 22. Results This study revealed mean age of participants was 49.21 years, 60% of the respondents were female, 40% were from Janajati and 87% belongs to Hindu religion, 63% of the respondents were receive fourth or more chemotherapy cycle and 40.62% missed chemotherapy due to sickness. Majority 98% of the respondents had get therapeutic communication, 18% missed chemotherapy due to holiday. 51% of respondents had medium level of adherence, 49% respondents had low level of adherence and none of the respondents had high level of adherence. There was no association between treatment adherence with demographics variables. Conclusions This study concluded cancer patients had a low level of adherence on treatment. The factors related to low adherence are Forgot chemotherapy cycle, self-stopped chemotherapy, long-travel, symptoms relief, inadequate therapeutic communication, lack of social support, chemotherapy side effects, financial problem, government holiday and unavailability of bed. concerned authorities need to emphasis on treatment adherence awareness, supportive program to public and address to strengthen treatment adherence.